Hearts, neck posture and metabolic intensity of sauropod dinosaurs. - Seymour, R S (2000)
Hypothesized upright neck postures in sauropod dinosaurs require systemic arterial blood pressures reaching 700 mmHg at the heart. Recent data on ventricular wall stress indicate that their left ventricles would have weighed 15 times those of similarly sized whales. Such dimensionally, energetically and mechanically disadvantageous ventricles were highly unlikely in an endothermic sauropod. Accessory hearts or a siphon mechanism, with sub-atmospheric blood pressures in the head, were also not feasible. If the blood flow requirements of sauropods were typical of ectotherms, the left-ventricular blood volume and mass would have been smaller; nevertheless, the heart would have suffered the serious mechanical disadvantage of thick walls. It is doubtful that any large sauropod could have raised its neck vertically and endured high arterial blood pressure, and it certainly could not if it had high metabolic rates characteristic of endotherms.